The Biosynthesis of Heterophyllin B in Pseudostellaria heterophylla From prePhHB-Encoded Precursor - Zheng, Wei; Zhou, Tao; Li, Jun; Jiang, Weike; Zhang, Jinqiang; Xiao, Chenghong; Wei, Dequn; Yang, Changgui; Xu, Rong; Gong, Anhui; Zhang, Chen; Bi, Yan (Frontiers in Plant Science, 2019)
Plant cyclopeptides are a large group of small molecule metabolites found in a wide variety of plants, including traditional Chinese medicinal plants. However, the majority of the cyclopeptides have not been studied for their biosynthetic mechanisms, including heterophyllin B (HB), which is one of the active compounds existing in the tuberous roots of Pseudostellaria heterophylla. Here, we screened the precursor genes (prePhHB) of HB in P. heterophylla and identified its validity in vivo and in vitro. First, we developed a new method to screen the precursors of HB from 16 candidate linear peptides. According to transcriptome sequencing data, we identified the genes that encoded the HB precursors and confirmed that the prePhHB-coded linear peptide could enzymatically synthesize HB. Next, we generated the transgenic tobacco that expressed prePhHB, and the results showed that HB was detected in transgenic tobacco. Moreover, we revealed the prePhHB differential expression as the result of the difference in the content of HB in P. heterophylla. The mutation of prePhHB in P. heterophylla influences the synthesis of HB. These results suggest that the prePhHB-encoded linear peptide (IFGGLPPP) is a precursor of HB in P. heterophylla. These findings provide new ideas for the study of the linear structure of CPs and lay a foundation for the biosynthesis of HB.